Current design features of the basic dress - Pagaoa, Ammerson I.; Escano, Maria Monica R. (Quezon City College of Home Economics, University of the Philippines, 2009)
The study is about the current design features in men's dress shirts available in the local market. The main objective of the study was to identify features in dress shirts of selected men's clothing brands. Specifically, it aimed to: (1) identify style changes of today's men's shirts from the basic dress shirt, and (2) identify commonalities and differences of the features between the dress shirts of selected men's brands. The researcher used a descriptive research method in conducting the study which included personal/ocular observations. The major source of the data came from the documented styles of the dress shirts of selected men's labels. This study also used content analysis in evaluating the data gathered. The data collected were compared to the design features of the basic dress shirt to come up with a profile of the current features in men's dress shirts. The researcher found that the dress shirts now are more stylized in terms of style and fit. Changes from the basic dress shirt may be identified through the following features: (a) collar style, (b) long-sleeve cuff treatment, (c) shirt sleeve vents, (d) pocket, (e) opening edge: shirt closure, (f) bottom hem, and (g) shirt back styling. Although regular or straight point collars are still common, variations in collar styles and sizes are evident in the dress shirts of today. Stylized button-down collars can be seen. The plain button front edge opening of the basic dress shirt evolved into a placket button front opening. The cuffs of the modern dress shirts vary in height and have a reverse side of a different fabric for style and fashion. The sleeves of modern dress shirts also include bicep buttons and tabs for folding the sleeves up for versatility. Pockets are also a major add-ons to dress shirts, and some have flaps rarely seen in dress shirts of the past. Moreover, yokes and pleats and darts can be seen for fitting. Based on the results gathered and analyzed, the researcher found that there are indications that the basic dress shirt has evolved based on the samples selected from the local market. The researcher recommends further study on the sizing of dress shirts from these selected men's labels, especially with the growing popularity of the "Slim fit" size among dress shirt labels. Since Filipino men are becoming conscious of the fit of the dress shirt, the researcher recommends a study on how this trend affects the sizing standard of these men's labels in the production of their dress shirts. The researcher also recommends expanding the scope of the study to at least five (5) brands of dress shirts in the department store of SM North EDSA and Megamall, which share the same target market, style, and pricing.
Thesis (B.S. Clothing Technology)--University of the Philippines Diliman.
Keywords: Men's clothing